A study on environmental and economic impacts of using waste marble powder in concrete. (September 2017) - Singh, Manpreet; Choudhary, Kailash; Srivastava, Anshuman; Singh Sangwan, Kuldip; Bhunia, Dipendu
Abstract: Gainful utilization of waste marble powder in various construction practices has become a topic of interest in research areas. An overview of works reported regarding the use as partial replacement of sand and cement by marble powder in concrete is presented in the paper. Gaps in the studies to date have been pointed out. An environmental impact comparison of normal concrete with the use of marble powder as partial replacement of cement and sand is carried out using the UMBERTO NXT life cycle analysis software with ReCipe midpoint and endpoint methods. Finally, a detailed cost analysis study has been performed to justify the use of marble powder in concrete which has exhibited encouraging results in terms of strength and quality. It has also been found that the use of marble slurry in concrete reduces its environmental impact and is economically beneficial. Highlights: Review of studies on partial replacement of sand and cement by waste marble powder in concrete carried out. Environmental impact assessment of marble powder incorporated concrete. Detailed cost analysis of concrete. Gainful utilization of a waste material and reduction of environmental impact of concrete.